An evaluation of pre-construction contract variables influencing occupational safety & health performance in Malaysian design & build and design-bid-build construction projects - Thian, Kah Kien. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Construction industry has been traditionally portraying the character of " Four D Industry' - Dull, Dirty, Demanding & Dangerous while its rapid growth and high sensitivity compare to other sectors of the country's economy indicated it involved long term investment and risks. High frequency of accidents has incurred high costs and time loss to both the firms undertaking the construction project as well as to society. One of the most obvious reason leading to poor health and safety performance in local construction projects is the profit driven nature of construction firms which is in contrast to the high expenditure in the implementation of health and safety during the construction process.